2016
DOI: 10.1016/j.rse.2016.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ascending/descending pass bias in SMOS salinity data demonstrated by observing westward-propagating features in the South Indian Ocean

Abstract: a b s t r a c tThe European Space Agency (ESA) Soil Moisture and Ocean Salinity (SMOS) satellite has been providing data, including sea surface salinity (SSS) measurements, for more than five years. However, the operational ESA Level 2 SSS data are known to have significant spatially and temporally varying biases between measurements from ascending passes (SSS A ) and measurements from descending passes (SSS D ). This paper demonstrates how these biases are reduced through the use of SSS anomalies. Climatology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Various studies (e.g., Banks et al, ; Köhler et al, ; Tong et al, ) showed that satellite‐retrieved SSS is corrupted by systematic errors coming from ice and land contamination (Font et al, ; Gabarro et al, ; Oliva et al, ), radio frequency interference (RFI; Oliva et al, ), seasonal biases, or latitudinal biases mainly due to thermal drift of the instrument (e.g., Boutin et al, ; Gourrion et al, ; Reul et al, ). Those biases are difficult to characterize and several institutions provide satellite‐retrieved SSS products based on different correction methods (e.g., Kolodziejczyk et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Various studies (e.g., Banks et al, ; Köhler et al, ; Tong et al, ) showed that satellite‐retrieved SSS is corrupted by systematic errors coming from ice and land contamination (Font et al, ; Gabarro et al, ; Oliva et al, ), radio frequency interference (RFI; Oliva et al, ), seasonal biases, or latitudinal biases mainly due to thermal drift of the instrument (e.g., Boutin et al, ; Gourrion et al, ; Reul et al, ). Those biases are difficult to characterize and several institutions provide satellite‐retrieved SSS products based on different correction methods (e.g., Kolodziejczyk et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…All these factors lead to errors making the measurement accuracy aim of the mission of 0.1 in salinity over 10–30 days and 100–200km very challenging. A recent review of SMOS performance concluded that the accuracy aim has not been met globally but mostly achieved in regions within 45°S–45°N with SSTs higher than ~10°C (Mecklenburg et al ., ; for higher‐latitude colder waters see Köhler et al ., ; and for approaches to dealing with biases see Banks et al ., ; Kolodziejczyk et al ., ). Despite these challenges good SSS data are being obtained from SMOS, giving a global picture of the changing ocean salinity over the last 7 years.…”
Section: How Is Salinity Measured From Space?mentioning
confidence: 99%
“…These have been previously identified as Rossby waves (or possibly ocean eddies) based on SST and sea surface height observations from space and, as expected, they are also visible in the SSS anomalies. The propagation speeds derived from these data are consistent with theoretical estimates of Rossby wave speeds, typically ~5–10cms −1 depending on latitude and Rossby wave mode (see figure 6 of Banks et al ., ). Detecting these signals in SSS would not have been possible using in situ measurements.…”
Section: What Can Salinity Measured From Space Tell Us?mentioning
confidence: 99%
See 2 more Smart Citations